Identifying and ranking the circular supply chain implementation challenges using pythagorean fuzzy SWARA approach (case of study: pharmaceutical industry of Guilan province) - Samaneh Rash; Mostafa Ebrahimpour Azbari; Mohammad Rahim Ramazanian (تصمیم گیری و تحقیق در عملیات)
Purpose: Commercial and industrial organizations worldwide are under severe threat of instability. Unsustainability issues arise because of environmental disturbances such as climate change, global warming, resource scarcity, and ecological degradation. Circular Supply Chain (CSC) has gained momentum in recent years and serves as one of the most sustainable and innovative approaches to the manufacturing industry. Adoption of the CSC increases the social, economic, and environmental aspects of the production system and the supply chain. However, researchers have conducted significantly less research on identifying and exploring the multiple challenges to implementing CSC in developing countries. Therefore, this research investigates and evaluates the challenges of CSC implementation in the production sector. We have identified 29 CSC challenges in the literature review.Methodology: The research proposes the Pythagorean Fuzzy SWARA (PF-SWARA) technique. This technique prioritizes CSC adoption challenges based on their relative importance. We used the proposed method in the pharmaceutical industry of the Guilan province.Findings: In the final results of the research, Strategic Challenges (SCs) and operational and environmental challenges are prioritized.Originality/Value: This research serves as a step for industry practitioners to efficiently and effectively adopt a CSC.